Efficient detection of copy‐number variations using exome data: Batch‐ and sex‐based analyses. Issue 1 (11th November 2020) - Uchiyama, Yuri; Yamaguchi, Daisuke; Iwama, Kazuhiro; Miyatake, Satoko; Hamanaka, Kohei; Tsuchida, Naomi; Aoi, Hiromi; Azuma, Yoshiteru; Itai, Toshiyuki; Saida, Ken; Fukuda, Hiromi; Sekiguchi, Futoshi; et al.
Abstract: Many algorithms to detect copy number variations (CNVs) using exome sequencing (ES) data have been reported and evaluated on their sensitivity and specificity, reproducibility, and precision. However, operational optimization of such algorithms for a better performance has not been fully addressed. ES of 1199 samples including 763 patients with different disease profiles was performed. ES data were analyzed to detect CNVs by both the eXome Hidden Markov Model (XHMM) and modified Nord's method. To efficiently detect rare CNVs, we aimed to decrease sequencing biases by analyzing, at the same time, the data of all unrelated samples sequenced in the same flow cell as a batch, and to eliminate sex effects of X‐linked CNVs by analyzing female and male sequences separately. We also applied several filtering steps for more efficient CNV selection. The average number of CNVs detected in one sample was <5. This optimization together with targeted CNV analysis by Nord's method identified pathogenic/likely pathogenic CNVs in 34 patients (4.5%, 34/763). In particular,  among 142 patients with epilepsy, the current protocol detected clinically relevant CNVs in 19 (13.4%) patients, whereas the previous protocol identified them in only 14 (9.9%) patients. Thus, this batch‐based XHMM analysis efficiently selected rare pathogenic CNVs in genetic diseases. Abstract : Using exome sequencing of 1199 samples including 763 from patients, we identified pathogenic/likely pathogenic copy number variations (CNVs) in 34 (4.5%, 34/763) patients using two CNV‐detection algorithms (eXome Hidden Markov Model [XHMM] and Nord's method) with the optimization by batch‐ and sex‐based analyses.